2022
DOI: 10.1002/htj.22504
|View full text |Cite
|
Sign up to set email alerts
|

FHD flow and heat transfer over a porous rotating disk accounting for Coriolis force along with viscous dissipation and thermal radiation

Abstract: The prime concern of the current findings includes the effect of viscous dissipation and nonlinear thermal radiation on the study of ferrofluid flow and heat transfer past a porous rotating disk. The time‐independent flow of incompressible ferrofluid is modeled for the considered geometry, and via similarity transformations, the given system is converted to a dimensionless system of the nonlinear ordinary differential equations. Here, the findings are explored computationally with help of Maple software. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In this study, data are evaluated numerically through the Keller box difference scheme and analyzed that thermophoresis parameters exerted a dominant impact in the rotating frame, as equated to the non-rotating frame. More studies on the rotating channel flow can be found in [23][24][25][26][27][28]. Rotational transport is linked with healthy heart performance [29].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, data are evaluated numerically through the Keller box difference scheme and analyzed that thermophoresis parameters exerted a dominant impact in the rotating frame, as equated to the non-rotating frame. More studies on the rotating channel flow can be found in [23][24][25][26][27][28]. Rotational transport is linked with healthy heart performance [29].…”
Section: Introductionmentioning
confidence: 99%
“…Shaw et al [ 17 ] have studied impact of Entropy Generation and Nonlinear Thermal Radiation on Darcy–Forchheimer Flow of MnFe 2 O 4 -Casson/Water Nanofluid due to a Rotating Disk. Very recently Sharma [ 18 ] has studied FHD flow and heat transfer over a porous rotating disk accounting for Coriolis force along with viscous dissipation and thermal radiation. Ram et al [ 19 ] have possessed a Ferrofluid flow over a moving plate in a porous medium is theoretically investigated by solving the boundary layer equations with boundary conditions using Neuringer–Rosensweig model.…”
Section: Introductionmentioning
confidence: 99%
“…Some very recent related studies can be found in [35][36][37][38][39][40][41][42][43][44] . Sharma et al 45 discussed the transfer of heat over a porous rotating disk and concluded that with the increase in the magnetic field, viscous dissipation, and the thermal radiation mechanism, the magnitude of the magnetic-fluid temperature is also increased. We may find some related studies in 46,47 .…”
Section: List Of Symbolsmentioning
confidence: 99%